Farelo de trigo e complexo enzimático na alimentação de poedeiras semipesadas na fase de produção - Araújo, Daniel de Magalhães [UNESP]; Silva, José Humberto Vilar da; Miranda, Edma Carvalho de; Araújo, Jose Anchieta de; Perazzo Costa, Fernando Guilherme; Magalhaes Teixeira, Elisanie Neiva (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2008)
The study was carried out with the objective to evaluate the effects of the inclusion of the wheat bran (WB) with or without supplementation of an enzymatic complex (EC) on the performance of semi-heavy hens in the egg-production phase. A total of 288 Lohmann Brown pullets were used, distributed to a completely randomized design in 4 x 2 factorial arrangement, composed by four WB levels (0, 3, 6 and 9%) in the ration and enzymatic complex supplementation (0 or 100g/100 kg diet), with eight treatments and six replicates of six birds. The enzymatic complex contained the enzymes beta-galactosidase, galactomananase, xilanase and alpha-glucanase. Feed intake, final body weight, egg production, egg weight, egg mass, egg mass feed conversion or egg dozen feed conversion was not affected by WB inclusion in the diets. Egg shell specific gravity deteriorated as WB levels increase in the diets. None of the characteristics was affected by the enzymatic complex supplementation, except for egg weight, that improved from 62.74 to 64.28 g. Then, the use up to 9.0% of wheat bran in the ration is recommended for semi-heavily chickens in the production phase. The supplementation of alpha-galactosidase, galactomannanase, xylanase and alpha-glucanase improve egg weight.
Wheat bran and enzymatic complex in the feeding of laying hens in the production phase
Keywords: alternative feedstuff; egg production; exogenous enzymes